Koniag-Pacific Eskimo bibliography - Clark, Donald W. (Donald Woodforde), 1932-2018 (Mercury series., 1975)
A listing of approximately 500 published and manuscript sources on the history and anthropology of the Pacific Eskimo, with extra focus on the Koniag, their Kodiak Island habitat, and in general on the history of the Kodiak region.